NUMERICAL SIMULATION STUDY LAMINAR MIXED CONVECTION NANOFLUIDS FLOW FORWARD-FACING STEP PLACED WITH BAFFLE - MOHAMAD SAUPEE, NURUL SYAZWANEE (IRC, 2018)
Numerical simulation study of laminar mixed convection flow using 3D channel in horizontal forward facing step by using different types of nanofluids placed with a baffle. The water was utilized as a base fluid and three types of nanofluids Silicon Dioxide ( ), Aluminium Oxide ( ) and Copper Oxide (CuO) also different nanoparticle diameters have been used in range of 20-80 nanometers. The various range of nanoparticles volume fraction in between 0.01 to 0.04. The Finite Volume Method (FVM) with SIMPLE Algorithm method was selected by using second order central differencing and solved the momentum and energy equations. The effects of baffle height and baffle width on velocity and temperature numerically simulated. The different geometry shape of baffle with first geometry baffle with 5mm height and 4mm width, second geometry baffle with 5mm height and 8mm width and the third geometry baffle with 8mm height and 2mm width have been created and identified. The numerical study and experimental results reveal that Silicon Dioxide ( ) has the highest Nusselt number increases with the increase of volume fraction. The most sufficient and relevant for is when the nanoparticle diameter size reduces it will significantly decrease the nanoparticle density. The numerical results study denote in a good agreement with the experimental results.